The Characterization of Mechanical and Chemical Properties of Recycled Styrofoam Waste Employing Extrusion Process - Budi Triyono; Destri Muliastri; Devi Eka Septiyani Arifin (Mechanical Engineering Department - Semarang State Polytechnic, 2023)
Styrofoam waste is a polystyrene plastic-based waste in the form of foam with low density. Scavengers or recyclers are not interested in receiving styrofoam waste because of its light density which makes it ineffective in transportation and storage. Styrofoam waste can actually be converted into solid polystyrene products through a thermal-extrusion process but data regarding the optimum operating temperature and the characteristics of the resulting solid polystyrene products are not yet available. The purpose of this study was to investigate the properties of solid polystyrene products resulting from recycled styrofoam waste and determine the optimum temperature of the thermal-extrusion treatment process to be compared with the characteristics of the original polystyrene based on the results of tensile and impact tests. In this study, the processing was carried out using the thermal-extrusion method; Styrofoam is melted and extruded into a mold to produce polystyrene solids. The research was carried out with variations in extrusion temperature at 180°C, 200°C, and 220°C. The polystyrene solids are then molded into tensile and impact test specimens by injection molding. The results showed that the optimal extrusion temperature was 200°C with tensile and impact strength values of 27.55 MPa and 1,069 j/m2, respectively. Compared to the original polystyrene, the tensile strength value is 25.3% lower and the impact strength value is 29.5% lower. The decrease in the tensile and impact strength values is due to the shortening of the molecular bonds in the recycled polystyrene during the thermal-extrusion treatment process. Even though the tensile strength and impact are still lower, the use of styrofoam waste using the thermal-extrusion method has the potential to be developed at the production and commercialization stage because the resulting product has good economic value and can also reduce the use of original polystyrene and at the same time can solve the problem of styrofoam waste.